Lame ducks and divided government: How voters control the unaccountable - Mark Schelker (Center for Economic Studies and ifo Institute (CESifo), 2011)
The ability of voters to use the available electoral instruments is crucial for the functioning of democracies. The paper shows that voters consider the institutional environment when making electoral decisions. Voters recognize that executives who face binding term limits (i.e., lame ducks) have incentives to deviate from the preferences of voters because these politicians are not subject to reelection restrictions. This weakened accountability can be counterbalanced by an alternative mechanism known as divided government. By dividing government control between the executive and legislative branches, voters can force a lame duck to compromise on policies with an opposing legislature. Using a panel data analysis of the US states from 1975 to 2000, it is shown that the probability of divided government is 10-15 percent higher when governors are lame ducks. This effect remains robust and significant even after controlling for many relevant covariates. This result provides evidence of the considerable capacity of voters to process information and use alternative electoral instruments to control an otherwise unaccountable executive.
Keywords: D72; 330; divided government; lame duck; term limit; accountability; Wahlverhalten; Regierung; Kompetenz; Zeit; Teilstaat; USA